The Use of Loan Loss Provisions for Capital Management, Earnings Management, and Procyclicality of Banks from UK and HK - Xiong, Shuye (2013)
The loan loss provisions is an important account which deals with the credit risks of the banks, and could be related to the accounting issues, capital management , earnings management and the economic recessions. Since the several financial crisis happened, there comes out more attention to the loan loss provisions study in the banking industry. In this dissertation, it detects whether UK banks and HK banks have used the loan loss provisions being the tool to do the capital management and the earnings management and also to find out the procyclicality pattern of them in the case of loan loss provisions. For doing so, it selects different variables to stand for different functions by using the GMM model. The results here show that the bank managers in UK and HK don not use the LLPs as the tool to do the capital management and the earnings management, however the procyclicality patter do exist in both UK and HK. And by the comparison, it gets out more issues related to agency theory, compensation policies and incentives mechamism of bank managers in UK and HK.